PEMODELAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PERGURUAN TINGGI POLITEKNIK - Subyantoro, Eko; Putra, Septafiansyah Dwi (Prosiding Seminar Nasional Darmajaya, 2017)
Higher Education is a place for students to get education to gain knowledge in the field of certain science. Parents entrust their children who are his assets to the best colleges. For Higher Education is the belief of parents to be an option, thus it can be said parents and students are the main customer for Higher Education.This research produces a CRM model for Higher Polytechnic University to monitor the result of learning achievement so Stakeholders can see the learning result both academic and non academic. Information systems development methodology FAST is a development with functional analysis of parts associated with the system. Fast method can be developed to facilitate the making of CRM model in Polytechnic..Â Keywordsâ3-5 keywords, Algorithm A, B algorithms, complexity